Nephrotoxicity: protection of silica nanoparticles loaded sodium salicylate and ginger in experimental rats - Eman Refraat Youness (Journal of Global Pharma Technology, 2019)
Background: Ultrasound-assisted sol−gel method was used to prepare hollow structured porous silica nanoemulsion loaded with sodium salicylate as a model drug. Objective: This work was extended to achieve the target of the current work via investigating the protective role this nanoemulsion model as anti-inflammatory drug or ginger for its antioxidant effect against cisplatin-induced nephrotoxicity in male albino rats. Results: The results clarify that the nanoemulsion model was synthesized using ultrasonic assisted with small size and well stabilization as proved by TEM and DLS analysis. Additionally, blood urea and serum creatinine were increased after cisplatin injection with disorders in oxidative stress and rising of homocysteine levels. Also, histopathological changes of the kidney tissue were observed. These changes back to normal via treatment with silica nanoparticles loaded sodium salicylate (Si-Sc-NPs), ginger or both. Oil /water nanoemulsion of (Si-Sc NPs) and ginger showed a protective and promising preventive strategy against nephrotoxicity due to their antioxidant and anti-inflammatory effects.